Determination of Optimum Temperature of Barrel Heater forReducing Waste in Plastic Injection Molding Process of Tractor Turn Signal Cover Parts using DMAIC Techniques - Semsri, Aphichit (Engineering and Technology Horizons, 2022)
Abstract This research aims is to reduce waste in the plastic injection molding process of tractor turn signal cover parts. The researcher used 7QC tools with DMAIC techniques to reducing waste below the target of 1 percent. The experimental research design was a 2k factorial at the 2-level. The research findings pointed out that the main cause of the waste problems was a silver spark accounting for 53.27 percent. Besides, the appropriate values of the factor level for using should be heater 1 temperature is 210°C, heater 2 temperature is 220°C, heater 3 temperature is 225°C, and heater 4 temperature is 246°C. In addition, in a true experiment with the plastic injection molding process of tractor turn signal cover parts, it reduced from 0.80 percent to 0.31 percent. It means that the waste decreased from the original accounting for about 61.25 percent. After the improvement process, the amount of waste was reduced to 0.83 percent from 1.51 percent or reducing of 45.1 percent. When compared to the goals of the company waste less than 1.00 percent found that it can achieve the goals set. After the improvement, waste occurred at 0.83 percent.